Florida Peach and Nectarine Varieties - Ali Sarkhosh; Mercy Olmstead; Jose Chaparro; Pete Andersen; Jeff Williamson (EDIS, 2018)
The Florida stone fruit breeding program began in 1952, under the direction of Dr. Ralph Sharpe. The major goal of Dr. Sharpe’s breeding program was to take advantage of the climate in Florida to provide early, high-quality fruit to the market (Sherman et. al., 1996). In 1966, Dr. Wayne Sherman became the leader of the stone fruit breeding program, and he continued to focus on breeding for low-chill peach cultivars with non-melting flesh that perform well in Florida’s subtropical climate. The current stone fruit breeder, Dr. Jose Chaparro, has overseen and initiated research to bring in unique plant material that focuses on large, high-quality fruit with disease resistance and low chilling requirements. Peaches and nectarines are the same species, Prunus persica, but nectarines differ from peaches in that they lack “peach fuzz.” Therefore, the following discussion applies to both peaches and nectarines, but in most cases reference will be made only to peaches. This 17-page publication is a minor revision written by Ali Sarkhosh, Mercy Olmstead, Jose Chaparro, Pete Andersen, and Jeff Williamson, and published by the Horticultural Sciences Department, October 2018.